Guest Comments on Online Travel Agents Regarding the Front Office Department Service at Melia Bali Hotel - Dwipayana, I Made Brahmantara; Adi, Ida Ayu Sri Puspa; Priliani, Ni Luh Dita (Journal of Hospitality Accommodation Management (JHAM), 2025)
This research aims to evaluate guest comments on Online Travel Agents (OTAs) regarding the Front Office Department service at Melia Bali Hotel, Indonesia. The study uses a descriptive qualitative research method to assess guest comments obtained from OTA platforms such as Tripadvisor, Booking.com, and Tiket.com during the period from 2018 to 2023. Data collection techniques for this research involve observation and documentation, focusing on analyzing guest comments and identifying patterns in guest expectations regarding the Front Office Department service. The results indicate that there are positive comments related to the quick check-in and check-out processes, staff friendliness, and prompt service. Conversely, negative comments were found regarding slow check-in processes, reservation discrepancies, and a lack of information about hotel facilities. Based on these findings, it is hoped that recommendations can be made to improve the Front Office Department service at Melia Bali Hotel, thereby enhancing guest satisfaction and serving as a reference for future research in the hospitality field, particularly concerning the evaluation of positive and negative guest comments on OTAs regarding Front Office Department services.